Mutu Fisikokimia & Organoleptik Es Krim Buah Kundur (Benincasa hispida) - Jaya, Bill Loren; Hartati, Fadjar Kurnia; Prayudanti, Adhania Andika (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2025)
Ice cream is a popular food product, but innovation using local ingredients remains limited. This study evaluates the effect of winter melon (Benincasa hispida) addition on the physicochemical and organoleptic qualities of ice cream to support product diversification and enhance nutritional value. The research employed a Randomized Block Design (RBD) with variations: 10% and 25% winter melon in diced or puréed forms. Parameters analyzed included melting rate, Overrun, crude fiber content, vitamin C levels, and organoleptic tests (taste and mouthfeel) using a hedonic scale (25 panelists). Results showed that P1 (10% diced winter melon) yielded the best performance with the highest organoleptic scores (taste: 4.08; mouthfeel: 4.29) and the highest total effectiveness (0.720). P2 (25% diced winter melon) recorded the highest vitamin C and crude fiber content but had lower organoleptic acceptance. Formulations P3 and P4 (puréed winter melon) showed balanced results but did not surpass P1. The P1 formulation, combining whipped cream, low-calorie sugar, and 10% diced winter melon, was the best combination, meeting physical, chemical, and organoleptic quality standards. The use of winter melon not only enhances the nutritional value of ice cream but also supports diversification based on local resources.Keywords - Ice Cream, Wax Gourd, Benincasa hispida, Physicochemical Quality, Organoleptic.